2020
DOI: 10.1016/s0140-6736(20)32227-3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of seasonal malaria chemoprevention at scale in west and central Africa: an observational study

Abstract: Summary Background Seasonal malaria chemoprevention (SMC) aims to prevent malaria in children during the high malaria transmission season. The Achieving Catalytic Expansion of SMC in the Sahel (ACCESS-SMC) project sought to remove barriers to the scale-up of SMC in seven countries in 2015 and 2016. We evaluated the project, including coverage, effectiveness of the intervention, safety, feasibility, drug resistance, and cost-effectiveness. Methods For this o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
109
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(135 citation statements)
references
References 16 publications
9
109
0
7
Order By: Relevance
“…There is general evidence that SMC is effective in reducing the episodes of P. falciparum malaria, with a Cochrane review ( Meremikwu et al, 2012 ) reporting that SMC was effective in reducing the incidence of malaria by approximately 75 % in children under 6 years of age during the transmission season in areas with seasonal malaria transmission. Another study ( Access-SMC-Partnership, 2020 ) also reported reduced mortality. Subsequent reviews concurred on the benefits of SMC ( Ashley and Poespoprodjo, 2020 ; Gutman et al, 2017 ; McCann et al, 2020 ), with reports of prevalence reduction by 65 % and incidence reduction by 80 % following SMC ( Greenwood, 2017 ; York, 2017 ).…”
Section: Impact and Consequences Of Population-level Drug-based Interventions: Smc Mdamentioning
confidence: 87%
See 1 more Smart Citation
“…There is general evidence that SMC is effective in reducing the episodes of P. falciparum malaria, with a Cochrane review ( Meremikwu et al, 2012 ) reporting that SMC was effective in reducing the incidence of malaria by approximately 75 % in children under 6 years of age during the transmission season in areas with seasonal malaria transmission. Another study ( Access-SMC-Partnership, 2020 ) also reported reduced mortality. Subsequent reviews concurred on the benefits of SMC ( Ashley and Poespoprodjo, 2020 ; Gutman et al, 2017 ; McCann et al, 2020 ), with reports of prevalence reduction by 65 % and incidence reduction by 80 % following SMC ( Greenwood, 2017 ; York, 2017 ).…”
Section: Impact and Consequences Of Population-level Drug-based Interventions: Smc Mdamentioning
confidence: 87%
“…Challenges to evaluating the statistical and clinical impact of population-level drug-based interventions like SMC and MDA include monitoring impact on malaria burden, evaluating the clinical benefit of these interventions, and addressing whether these interventions can interrupt transmission ( WHO, 2013 , 2015 , 2017 ). Historically, the impact of SMC or MDA has been assessed based on epidemiological metrics like prevalence or incidence ( Access-SMC-Partnership, 2020 ) ( Supplemental Table 1 ); however, these indicators may not reveal important changes to the parasite population and become more challenging to assess in certain contexts such as very low transmission settings. Measuring the impact of these interventions on clinical metrics like anemia or childhood mortality requires careful study designs that are powered to evaluate these outcomes ( Cohee et al, 2020 ).…”
Section: Drug Impact On Parasite Population Structurementioning
confidence: 99%
“…Community-based trials in diverse areas of West Africa where malaria is highly seasonal have demonstrated that the effect of intensively-delivered SMC on clinical incidence and parasite prevalence should be substantial. [24][25][26] Although there are many challenges to optimal implementation in northern Nigeria where malaria is most seasonal, it is notable that SMC has been safely and effectively delivered to children up to the age of 10 years in trials in Senegal, 27 so potential benefits of expanding the age coverage in Nigeria should be considered, while continuing efforts to establish effective delivery to younger children as currently intended.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to established methods, seasonal malaria chemoprevention (SMC) targeted to children under five years of age became a policy from 2014 onwards in several of the northern states where malaria prevalence has remained high, but only very limited implementation occurred in a few states before the 2018 survey. Community-based trials in diverse areas of West Africa where malaria is highly seasonal have demonstrated that the effect of intensively-delivered SMC on clinical incidence and parasite prevalence should be substantial 24-26 . Although there are many challenges to optimal implementation in northern Nigeria where malaria is most seasonal, it is notable that SMC has been safely and effectively delivered to children up to the age of 10 years in trials in Senegal 27 , so potential benefits of expanding the age coverage in Nigeria should be considered, while continuing efforts to establish effective delivery to younger children as currently intended.…”
Section: Discussionmentioning
confidence: 99%